Proposal of mobile technology-based electronic vaccine card for process optimization and data availability (Brazilian Journal of Health Research, 2021)
Introduction:Recording and consolidating vaccination data are challenges faced by different health agencies, nowadays. In addition to the likelihood of having these data lost, either by patients or healthcare units, their availability is compromised, which makes it impossible for health institutions to take strategic measures to serve the population. Thus, health institutions strongly demand finding an accessible solution capable of standardizing and makinges such records available. Objective: Presenting the development of a mobile application accessible to the population, through which individuals would be able to virtually access their immunization data. Methods: Based on bibliographic research and literary review, the current study focused on immunizations and application planning. Thus, the stage associated with App Inventor App using, as a programming tool, was developed. Finally, the application was developed and the feasibility was evaluated. Results: The developed application has successfully enabled data, standardization and availability via Cloud Computing. Information about vaccines and the insertion of reminders about upcoming immunizations are functions enabling greater adherence to the national immunization program. The implemented structure helps the analyzed process and enables technological expansions, such as Artificial Intelligence, used to optimize campaign strategies. Conclusion: The present study is expected to help developing computerized systems, equipped with mobile resources, as well as emphasizes the relevance of creating an accessible and standardized database, to help defining the immunization rate achieved by investigated societies concerning certain vaccines.
Keywords: Vaccination; Immunization; Mobile Applications; Cloud Computing; Database